Roflumilast, ursodeoxycholic acid and nucleinate efficiency in patients with chronic obstructive pulmonary disease with accompanying chronic non-stone cholecystitis. - T. V. Dudka; O. S. Huhlina (Medičnì Perspektivi, 2014)
Global Initiative for diagnosis, treatment and prevention of COPD has recently included roflumilast (R) - an inhibitor of phosphodiesterase-4 (PDE-4) as a new therapeutic agent to the recommendations for the management of patients suffering from COPD with severe and moderate course. Objective. To investigate the efficacy of roflumilast, ursodeoxycholic and ribonucleinic acids  in patients with COPD with an accompanying chronic non-stone cholecystitis. Materials and methods. The study involved 40 patients with COPD stage II-III, in the acute phase with an accompanying CNC in the acute phase and 20 practically  healthy individuals (PHI). Patients of the control group (group 2) received berodual, UA500 mg overnight for 30 days, under the conditions of infective exacerbation of COPD - antibiotic therapy. Group 1 (study, 20 people) received roflumilast 500 mg additionally once  a day, nucleinas 500 mg 3 times daily for 30 days. Results and discussion. The results obtained in the study of the dynamics of treatment and their analysis indicate that exposure to complex therapy, amelioration, reducing the signs of exacerbation of COPD and CNC, a significant improvement of quality of life in patients of group 1 were noticed sooner. Figures of external respiration functions(FER)  in dynamics of treatment in patients with COPD with an accompanying CNC show higher efficiency of the proposed therapy too. In particular, the rate of forced expiration for the first second after treatment in patients of group 1 increased by 31,5% (p<0,05), while patients in group 2 - by 14,0% (p<0,05) probable presence of intergroup differences (p<0,05). Taking into consideration the fact that the treatment of patients of group 1 included antioxidant preparation H - dynamic performance and the intensity of lipid peroxidation were significantly different from baseline in all periods of observation. For instance, the content of MA (malonic aldehyde) in plasma after treatment in group 1 decreased by 1,7 times (p<0,05), while in group 2 - 1,2 times (p<0,05) with significant difference between groups (p<0,05). Biochemical analysis of blood and bile for bilirubin after treatment indicates its significant reduction in patients of group 1 - by 1,7 times in blood (p<0,05) and 27,7% (p<0,05) in  bile.In patients of group 2, due to the influence of the UA, bilirubin in bile decreased by 7,8% (p<0,05), and the content of bilirubin in  blood decreased by 13,0% (p<0,05). Conclusions. The use of roflumilast in combination with berodual, ursodeoxycholic and ribonucleinic acids in patients with COPD and in acute CNC promoted faster, than under conventional therapy (6-7 days), elimination of symptoms of both acute comorbid conditions. Combined therapy of patients with COPD stage II-III of the CNC in the acute phase, which included inhalation therapy with berodual, ursodeoxycholic acid, roflumilast and nuclineas helped to reduce the intensity of oxidative stress, endotoxemia, renewed the activity of the components with antioxidant protection and natural detoxification system.